PENGGUNAAN GOOGLE TRANSLATE SEBAGAI ALTERNATIF MEDIA PENERJEMAH PADA ABSTRAK JURNAL MAHASISWA - Selfiana Triyanty Ndapa Lawa; Christmas P. Ate; Viktorius P. Feka (FKIP Universitas Citra Bangsa, 2022)
AbstractThe aim of this study is to describe the use of google translate as an alternative medium for translating Indonesian to English texts in students’ journals. This study uses a qualitative method with a descriptive approach. The instruments used in this research are questionnaire, interview and documentation. The results 80% stated the results of the translation using google translate were